Dimensions of transformation in the Ottoman Empire from the late medieval age to modernity (Leiden ; Boston)
xxxix, 475 sayfa
Keywords: “Eighteen expert researchers have come together to provide original articles and new perspectives on transformation throughout Ottoman history in order to honor the life's work of Metin Kunt. Kunt's work revolutionized our understanding of change in Ottoman political, social and cultural history in the late 16th and early 17th centuries. This new collection focuses on the contributions of key players in these fields and includes chapters on Ottoman artisans in a changing political context, Ottoman chief scribes and the rhetorics of political survival in the 17th century, and empiricism in the Ottoman Empire“ --